Ustrojowy czynnik rozwoju prawa rolnego - Budzinowski, Roman (Wydawnictwo Naukowe UAM, 2007)
The objective of the study was to provide general assessment of the role of constitutional provisions regulating agriculture in the shaping of agricultural law. The author first analyses relevant provisions in selected European constitutions and then discusses article 23 o f Poland's Constitution in more detail. Article 23 provides that the basis o f the agricultural system o f the State is the family farm. Looking for guidelines how to construe this constitutional 'agricultural' provision, the author quotes other provisions, and in particular the one which describes the social market economy as the basis of the economic system. The agricultural system (as well as the agricultural market) is an element o f a social market economy. Thus agriculture is also part o f the national economy, which means a departure from the strictly liberal attitude to it, allowing for certain corrections, or adjustments o f the market rules. In conclusion the author states that the provisions o f Poland's constitution justify an agricultural policy whose aim is to ensure that agriculture enjoys more favourable development conditions than those secured by the available market mechanisms. Such a policy is based on the need to take account o f the specificity o f agriculture that makes it so distinct from other sectors o f the economy. The actual role o f the Constitution o f the Polish Republic in the development o f agricultural law is not significant. As the legislative experience has shown so far, while the 'corrective' function o f the 'agricultural' provision of Poland's Constitution is very clear, its creative function is not at all pronounced. On the other hand, the recent years have proved a growing importance o f the international, and in particular European factor, in the development of agricultural law in Poland.